Integration of mesenchymal stem cells into islet cell spheroids improves long-term viability, but not islet function. Issue 5 (3rd September 2017) - Rawal, Sonia; Williams, S. Janette; Ramachandran, Karthik; Stehno-Bittel, Lisa
ABSTRACT: Pancreatic islets, especially the large islets (> 150µm in diameter) have poor survival rates in culture. Co-culturing with mesenchymal stem cells (MSCs) has been shown to improve islet survival and function. However, most co-culture studies have been comprised of MSC surrounding islets in the media. The purpose of this study was to determine whether islet survival and function was improved when the 2 populations of cells were intermingled with each other in a defined geometry. Hybrid spheroids containing 25, 50 or 75 or 90% islets cells with appropriate numbers of MSCs were created along with spheroids comprised of only islet cells or only MSCs. Spheroids were tested for yield, viability, diameter, cellular composition, and glucose-stimulated insulin secretion. The 25% islet/75% MSC group created the fewest spheroids, with the poorest survival and insulin secretion and the largest diameter. The remaining groups were highly viable with average diameters under 80µm at formation. However, the hybrid spheroid groups preferred to cluster in islet-only spheroids. The 50, 75 and 90% islet cell groups had excellent long-term survival with 90–95% viability at 2 weeks in culture, compared with the islet only group that were below 80% viability. The glucose-stimulated insulin secretion was not statistically different for the 50, 75, or 90 groups when exposed to 2.4, 16.8, or 22.4 mM glucose. Only the spheroids with 25% islet cells had a statistically lower levels of insulin release, and the 100% had statistically higher levels at 22.4 mM glucose and in response to secretagogue. Thus, imbedded co-culture improved long-term viability, but failed to enhance glucose-stimulated insulin secretion in vitro .